Development Animated Dubbing Video as Learning Media in English Speaking at Senior High School - Boy Santuri; Widiarini; Istina Atul Makrifah; Ahmad Saifudin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
This research was motivated by the results of the needs analysis at MAN 1 Blitar. Researcher found several problems faced by students in the process of learning English. This study aims to determine the opinion of the validators, the response of teacher and students to the learning media that has been developed in the form of Video Dubbing Animation. The research method used is Research and Development (R&D) using the ADDIE model by Dick and Carry. The media that has been developed consists of two videos, one video to explain the material and one dubbing video as a student assignment. The material presented in this product is a narrative text focused on speaking skills. Data collection techniques were carried out using interviews and surveys. The instruments used are interview guidelines and questionnaires using a Likert scale. Based on the results of validation carried out by material experts and media expert, then the results of teacher and student responses, the percentage of results obtained were 80%, 94%, 86% and 66.7% with a total score of 81.7% where the score reached the criteria of